Eosinophil granuloma due to parasite treated by laparoscopic and endoscopic cooperative surgery: a case report - Toshikatsu Tsuji; Noriyuki Inaki (Surgical Case Reports)
Abstract Background Gastric eosinophilic granuloma caused by parasitic infection is rare. It is often suspected to be a malignant disease and it is difficult to diagnose. We successfully diagnosed and removed a gastric eosinophilic granuloma using laparoscopic and endoscopic cooperative surgery (LECS). Case presentation A 35-year-old woman visited our hospital because of epigastric pain. Upper gastrointestinal endoscopy revealed a 15 mm submucosal tumor (SMT) with changes in the folds, such as enlargement and convergence, located in the greater curvature of the lower gastric body. Computed tomography (CT) showed a dense, nonenhanced area of 15 mm at the same site. SMT was suspected, but undifferentiated cancer could not be excluded. We performed laparoscopic partial gastrectomy using LECS for resection biopsy. Histopathological examination showed an SMT 8 × 8 × 5 mm in size with an unclear boundary and necrosed insects at the core of the tumor. There was marked eosinophilic infiltration around the area. The diagnosis was gastric granuloma caused by parasitic infection. Conclusions It is difficult to differentiate gastric eosinophilic granuloma caused by parasitic infection from malignant disease. In this case, LECS is considered a minimally invasive and useful procedure.